2009
DOI: 10.1007/s00125-009-1320-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atrophy of lower leg and foot muscles—a follow-up study of long-term diabetic polyneuropathy using magnetic resonance imaging (MRI)

Abstract: Aims/hypothesis The aim of the study was to determine the loss of muscle volume in the lower leg and foot in longterm diabetic patients in relation to the presence of neuropathy. Methods We re-examined 26 type 1 diabetic patients who had participated in magnetic resonance imaging (MRI) studies on muscle volume in the lower leg and foot 9 to 12 years earlier. Re-examination involved MRI, isokinetic dynamometry, clinical examination, electrophysiological studies and quantitative sensory examinations. Results Ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
4
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 40 publications
11
105
4
2
Order By: Relevance
“…Conversely these dependencies, if severe, may confound imaging assessment of outcome by masking changes due to disease. In our healthy volunteers, consistent with age-related impaired muscle strength and neurophysiological performance [4, 45], muscle MTR reduced while T 2 and FF increased with age in both thigh and lower leg muscles. Schwenzer et al [25] also demonstrated increases in calf-level FF and T 2 in older subjects, but not MTR.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely these dependencies, if severe, may confound imaging assessment of outcome by masking changes due to disease. In our healthy volunteers, consistent with age-related impaired muscle strength and neurophysiological performance [4, 45], muscle MTR reduced while T 2 and FF increased with age in both thigh and lower leg muscles. Schwenzer et al [25] also demonstrated increases in calf-level FF and T 2 in older subjects, but not MTR.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown atrophy of the ankle plantar and dorsiflexor muscles and knee extensors in patients with diabetic neuropathy compared with patients without neuropathy and control subjects (2,4,6,8). However, the effect on more-proximal leg muscles (knee extensors and flexors), which confer a major effect on postural stability and gait performance, has not been established.…”
Section: Introductionmentioning
confidence: 86%
“…13 Andreassen et al reported that DN could be involved in the accelerated muscle atrophy of lower extremities, but no difference was observed for the muscle quality between neuropathic and non-neuropathic patients. 14 These findings suggest that DN may have an adverse effect on mobility through sarcopenia in patients with diabetes. Also, DR may be a cause for mobility limitations, and the association between visual impairment and sarcopenia has been reported.…”
Section: Pathophysiology/complicationsmentioning
confidence: 93%